Subjective expectations from radiotherapy and chemotherapy in patients with oncological illnesses - E. Rasskazova; M. Kovyazina; M. Karakurchi (European Psychiatry, 2022)
Introduction Expectations and fears about chemotherapy and radiotherapy in patients with oncological illness may not only affect their subjective well-being (Shaverdian et al., 2018) but also treatment satisfaction and complaints of side effects (Guidolin et al., 2018, Dong et al., 2014, Colagiuri et al., 2013).